Health and safety leadership strategy : how authentically inclusive leaders inspire employees to achieve extraordinary results? - Carrillo, Rosa Antonia (New York, NY : Routledge, 2023)
"The purpose of this book is to awaken leaders to the unique opportunities now present in the areas typically delegated to Health & Safety. It is a strategy to utilize existing resources to fully develop and engage human potential to catapult business achievement. The confluence of COVID-19, the resulting burnout, the attention on diversity, equity and inclusion generated by the Black Lives Matter movement and the 'great resignation' which continues to create openings to fundamentally change how we address personal development, sustainable growth and social responsibility. The argument within is that the better we manage the social aspects of the organization, the better our business results. Elucidating to the reader the societal shifts of workplace culture in recent years, this text expertly analyses the importance of mental health in the workplace, whilst also explaining how management and HR departments can improve. It examines who is responsible for generating psychological safety and provides relationship strategies that will improve performance. The critiques in this text establish why it is imperative for business leaders to concentrate on how their company culture affects their employees, and whether their employees feel safe, seen and supported. The concepts and practices in this book are the ones that leaders have used across the ages to create commitment, accountability, and excellence. Managers will benefit from a deeper understanding of how these issues impact every aspect of organizational performance. This book is essential reading for executives, leaders and those interested in leadership. They could be in the C-suite, operations, health & safety and HR. It is also directly relevant to organization development and change management specialists interested in including safety within their practice"--
Keywords: Leadership; Work environment -- Psychological aspects; Personnel management; Employee motivation; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Leadership